Standing in the Need of Prayer: A Modern Retelling of the Classic Spiritual - Weatherford, Carole Boston, 1956-; Morrison, Frank, 1971- (New York : Crown Books for Young Readers, an imprint of Random House Childrens Books, 2022)
The popular spiritual, Standing in the need of prayer, has been reworked to chronicle the milestones, struggles, tragedies, and triumphs of African American people and their history. The text and illustrations of this inspirational book are informative reminders of yesterday, hopeful images for today, and aspirational dreams of tomorrow.
Keywords: African Americans -- Prayers and devotions; Juvenile literature; Spirituals (Songs) -- Juvenile literature; African Americans -- History; Juvenile literature; Sacred songs -- Juvenile literature; Prayer -- Juvenile literature; History; Juvenile works; Folk songs